A Validated RP-HPLC Method for the Estimation of Levetiracetam in Bulk and Pharmaceutical Formulations - A. Lakshmana Rao; V. Naga Jahnavi (E-Journal of Chemistry)
A rapid and sensitive high performance liquid chromatographic method was developed for the estimation of levetiracetam in bulk and pharmaceutical formulations. Levetiracetam was chromatographed on a reverse phase C18 column in a mobile phase consisting of 0.05 M KH2PO4 buffer (pH 3.0 adjusted with orthophosphoric acid) and methanol in the ratio 70:30 v/v. The mobile phase was pumped at a flow rate of 1.2 mL/min. with detection at 210 nm. The detector response was linear in the concentration of 20-120 μg/mL. The limit of detection and limit of quantification was found to be 0.0104 and 0.0317 μg/mL, respectively. The intra and inter day variation was found to be less than 1%. The mean recovery of the drug from the solution containing 100 µg/mL was 100.038 μg/mL. The proposed method is simple, fast, accurate, precise and reproducible hence can be applied for routine quality control analysis of levetiracetam in bulk and pharmaceutical formulations.